An Examination of Weight-Associated Memorable Messages, Sources, and Outcomes. Issue 5 (20th October 2017) - Russell, Jessica; Smith, Sandi W.
ABSTRACT: As college students are particularly vulnerable to weight struggles, understanding how weight-related communication impacts behavior can have important implications for overall health. This study investigated memorable messages regarding weight using the theoretical lens of control theory. Control theory provides a guiding framework to predict how memorable messages impact subsequent behavior when an individual senses a discrepancy between their ideal and actual weight. Participants were asked to report whether they had experienced a weight-associated discrepancy and if they recalled a memorable message about this issue. For those with a memorable message, characteristics and outcomes of the message were solicited. The prevalence of weight-associated discrepancies, associated memorable messages, topics, sources, and perceived intentions of the memorable messages and the reported outcomes of message recall were identified. Findings address the relationship between interpersonal communication and weight and offer insight to the role of memorable messages in both construction and achievement of individuals' ideal states.